Wielding the Willow: Processes of Institutional Change in English County Cricket - Wright, April L.; Zammuto, Raymond F. (Academy of Management Journal, 2013)
We examine institutional change processes through a longitudinal archival study of First-Class County Cricket in England. We find that institutional change occurs in mature organizational fields when organizations located at the field center, periphery, and in between trigger different multilevel processes. Our results show that when society-level evolutionary change created organization-level resource pressures that undermined the central values of a mature field, the group of actors between the field center and periphery served as intermediaries in the institutional change process bringing the societal, field, and organizational levels back into alignment. Our process model was supported over two cycles of change.